2016
DOI: 10.1103/physrevc.94.055807
|View full text |Cite
|
Sign up to set email alerts
|

α scattering and α -induced reaction cross sections of Zn64 at low energies

Abstract: Background: α-nucleus potentials play an essential role for the calculation of α-induced reaction cross sections at low energies in the statistical model. Uncertainties of these calculations are related to ambiguities in the adjustment of the potential parameters to experimental elastic scattering angular distributions and to the energy dependence of the effective α-nucleus potentials. Purpose: The present work studies the total reaction cross section σ reac of α-induced reactions at low energies which can be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 76 publications
(231 reference statements)
2
24
0
Order By: Relevance
“…It is found that the 6720 combinations under study show a wide range of χ 2 /F per data point from slightly below 8 to more than 4000 for all 43 experimental values for σ reac and the (α,n), (α,γ), and (α,p) reactions in [7,8]. These χ 2 /F correspond to an average deviation factor f dev between experiment and theory for all data points from about 1.3 for the best fits up to 2.6 for the worst cases.…”
Section: Experimental Datamentioning
confidence: 99%
See 4 more Smart Citations
“…It is found that the 6720 combinations under study show a wide range of χ 2 /F per data point from slightly below 8 to more than 4000 for all 43 experimental values for σ reac and the (α,n), (α,γ), and (α,p) reactions in [7,8]. These χ 2 /F correspond to an average deviation factor f dev between experiment and theory for all data points from about 1.3 for the best fits up to 2.6 for the worst cases.…”
Section: Experimental Datamentioning
confidence: 99%
“…The latest global A-OMP by Su and Han [33] is not yet implemented in TALYS. It has been shown in [7] that this potential overestimates the total reaction cross sections for 64 Zn at low energies. Thus, no efforts have been made to implement this potential into TALYS for the present study.…”
Section: α-Nucleus Optical Model Potentialsmentioning
confidence: 99%
See 3 more Smart Citations